Information And Communication Technology Mediates The Competence And Workers And Its Impact On The Productivity Of Corn Farming In Tojo Una - Una Regency - P. Adam, Fauziah; Darman, Saiful; P. Adam, Rosida; Antara, Made; Abd. Rauf, Rustam; Lamusa, Arifudin (International Journal of Science, Technology & Management, 2024)
The aim of this research is to analyze The influence of instructor competency and work motivation on mastery of information and communication technology and instructor performance and its impact on corn farming productivity in Tojo Una- Una Regency . Causality research method using the SEM-PLS approach. The research sample was 151 extension workers in Tojo Una-Una Regency. The research results show that of the 9 (nine ) research hypotheses there is 1 (one) hypothesis that is not significant, namely the motivation variable The work of extension workers has an effect but is not significant on the performance of agricultural extension workers in Tojo Una-Una Regency. Furthermore, the research results show that Information and Communication Technology mediates the influence of competency and Work Motivation, and the performance of instructors mediates the application of information technology on farming productivity.